Intrusion Detection and Prevention System to Increase the Detection Rate Using Data Mining Technique - Tiwari, Susheel Kumar; Kumawat, Chandikaditya; Shrivastava, Manish (International Journal of Computer Sciences and Engineering, 2025)
Intrusion Detection Systems are used to monitor computer system for sign of security violations over network or cloud environment. On detection of such sign triggers of IDSs is to report them to generate the alerts. These alerts are presented to a human analyst or user who evaluates the alerts and initiates an adequate response. In Practice, IDSs have been observed to trigger thousands of alerts per day, most of which are mistakenly triggered by begin events such as false positive. This makes it extremely difficult for the analyst to correctly identify alerts related to attack such as a true positive. Recently Data Mining methods have gained importance in addressing network or cloud security issues, including network intrusion detection and cloud Intrusion detection systems, these systems aim to identify attacks with a high detection rate and a low false alarm rate. Consequently, Unsupervised Learning methods have been given a closer look for network and cloud intrusion detection. We present unsupervised based Clustering Technique and compare with traditional centroid-based clustering algorithms for intrusion detection. These techniques are applied to the KDD Cup98 data set .In addition; a Comparative analysis shows the advantage of proposed approach over Traditional clustering-based Methods over in identifying new or unseen attack. Experimental result show that A.I based Hill Climbing aided k-means Clustering algorithm improves the detection rate in IDS than K-Mean algorithm and achieved 92% detection rate in IDS System